Pembaruan Teknologi Informasi Untuk Sistem Pendukung Keputusan Pemberian Kelayakan Kredit Menerapkan Metode Profile Matching dan Metode Fuzzy Mamdani - Rismadina Puspa; Nurahman Nurahman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The development of information technology is currently growing rapidly, with so many positive impacts on people's lives in general. With current developments, there are more and more community needs such as financial needs as well as personal needs. This can be seen from the information technology that provides convenience in many aspects of people's lives, including crediting. Each company usually faces very tough competition, as many credit companies have sprung up to lend funds and BPKB as collateral. DIVA Eletronic and Furniture are engaged in credit financing companies. Credit financing is an institution that provides temporary credit services in the form of guarantees. The company establishes policies in the credit extension process requiring consideration and analysis from the credit party based on regulations and the existence of credit financing policies. PT. DIVA Eletronic and Furniture is a subsidiary of PT. COLOMBUS with the aim of building a network of business units throughout the city that provides the most complete, quality and guaranteed goods. So with the number of consumers who began to increase so that the company experienced difficulties in managing data and in determining creditworthiness. Not infrequently due to errors in determining consumer eligibility, bad credit occurs so that companies have to withdraw electronic goods or furniture from the consumers themselves. So with that it intends to make with the title: Credit Information Technology Renewal for Decision Support System for granting creditworthiness at PT. DIVA Eletronic and Furniture with Profile Matching Method and Fuzzy Method